Importance Learning Education Citizenship in Creating National Character Education in Participant Elementary School Educators - Lubis, Wahida Suaiba (International Journal of Students Education, 2025)
Objective this study for know importance learning education citizenship in creating national character education for elementary school students. Character education is a the thing that require, because rated able to make participant students become intelligent, have good character and manners so that students are meaningful as members of society both for themselves and society in general and widely. Education national character that moral and well-mannered character sublime poured in subjects education citizenship which implemented in each level school. However in fact education character in Indonesia rated Fail in create man who have character and morals as in its mission. To overcome this, innovation is needed in the teaching and learning process, especially in civic education learning. in this scientific article, data collection was carried out using the literature study method. The results of this study indicate that the provision of civic education subjects can be used as a character builder for the indonesian nation for elementary school children.